Tinjauan Pelaksanaan Controlling (Pengawasan) Sistem Penjajaran Rekam Medis di Rumah Sakit Annisa Cikarang - Nurhaliza Putrikama; Deasy Rosmala Dewi; Puteri Fannya; Nanda Aula Rumana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Medical records are one of the important files in health care facilities, both in clinics, health centers and hospitals because they contain a patient's medical history. In order to keep these medical records available when needed, supervision is needed. Thus, from the supervision of the implementation of medical records in the filing room of hospital institutions, the process can be known, whether there are deviations or errors and the extent of errors that occur in the process. Research on the implementation of the Controlling (Supervision) medical record alignment system was carried out at the Annisa Cikarang Hospital. This study aims to determine how the supervision of the medical record alignment system at the Annisa Cikarang Hospital. This study uses a qualitative method with informants 1 medical record coordinator, 1 person in charge of filing and 6 officers in the filing room. The results of the research obtained are that there is no SOP for alignment and supervision that has not been carried out using an expedition book. Suggestions for the Annisa Cikarang Hospital are to add procedures in the alignment to be more detailed, and to have an expedition book to make it easier to track medical records.